Analysis of the Use of DeepSeek in Paragraph Patterns in Chinese Learning - Ravellia, Renita; Nirmalasari, Yohanna; Airlinda, Anggrah Diah (FKIP - Universitas Riau, 2025)
This technological development has a significant impact in various fields, especially in the advancement of the Chinese language. Chinese has paragraph patterns in its writing. This research aims to find out the Chinese paragraph patterns developed through DeepSeek artificial intelligence technology by Chinese language study program students. This research uses a qualitative approach by collecting data in the form of Chinese essay texts written by students using the help of DeepSeek. The results show that paragraph patterns can be divided into three, namely deductive, inductive, mixed paragraph patterns. In deductive paragraphs, there are two paragraph structures, namely first, KT (topic sentence)-KPL(direct developer sentence), this structure is not found in the data that the researchers studied, then the second KT -KPL-KPT (indirect developer sentence) is found in the data in this study. Furthermore, the inductive paragraph pattern has two paragraph structures, namely first, KPL -KT then the second KPT -KPL-KT. Meanwhile, the finding of mixed paragraph patterns is a special finding. This proves that despite using DeepSeek in its use, there are differences in paragraph structures developed by the technology.